2018
DOI: 10.1038/s41598-018-21722-1
|View full text |Cite
|
Sign up to set email alerts
|

Experimental study of the anti-tumour activity and pharmacokinetics of arctigenin and its valine ester derivative

Abstract: Arctigenin (ARG) is a functional active component that has important physiological and pharmacological activities. The anti-tumour and anti-inflammatory activities of ARG show good potential for application and development, but this material has the defect of low water solubility. In this experiment, the valine derivative of ARG (ARG-V) was designed and synthesized to overcome this disadvantage. The ARG amino acid, EDCI and DMAP were raw materials in the addition reaction, with a molar ratio of 1:2:2:0.5. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 43 publications
1
7
1
Order By: Relevance
“…After intravenous injection of arctigenin, the plasma concentration–time data in piglets conformed to the non-absorbed two-compartment model. These results were similar to those of a previous study, which evaluated intravenous injection of different doses of arctigenin and its valine ester derivative in Wistar rats (21). The blood drug concentration–time curve was consistent with the two-compartment model.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…After intravenous injection of arctigenin, the plasma concentration–time data in piglets conformed to the non-absorbed two-compartment model. These results were similar to those of a previous study, which evaluated intravenous injection of different doses of arctigenin and its valine ester derivative in Wistar rats (21). The blood drug concentration–time curve was consistent with the two-compartment model.…”
Section: Discussionsupporting
confidence: 91%
“…After oral administration of Fructus arctii, the blood concentration–time data of arctigenin in piglets were consistent with the two-compartment model of absorption. This is not in line with the characteristics of the one-compartment model after Wistar rats were orally administered different doses of arctiin and its valine ester derivative, which was reported by Cai et al (21). These differences may have been species specific.…”
Section: Discussioncontrasting
confidence: 56%
“…As we know, the potential toxicities of Arctigenin were reported previously. Repeated subcutaneous injection of large doses of Arctigenin can induce injury to the liver and biliary duct in Beagle dogs (Cai et al, 2018 ). Meanwhile, 7-day continuous oral exposure demonstrated that Arctigenin (9 mg/kg/day) evidently aggravated apoptosis in the kidney tissue, especially in tubular cells in kidney I/R mice, which implied that Arctigenin had potential renal injury effect (Han et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have established that there are three morphological categories of liver tumors in dogs [14][15][16][17]: (1) Massive tumors within a single lobe of the liver -this is the most well-verified category; (2) nodular or multifocal formations involving several lobes [18][19][20]; and (3) diffuse tumors occurring across the entire area of the liver [21][22][23][24]. If researchers gain more precise information about how the structural variability of liver tumors in dogs affects life expectancy, clinicians will be better able to make differential diagnoses of various liver pathologies and conduct necessary treatment on time [25][26][27][28][29].…”
Section: Introductionmentioning
confidence: 99%